Clinical Impact of Preoperative Sentinel Lymph Node Imaging With SPECT/CT in the Management of Interscapular Malignant Melanoma - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2015)
A 31-year-old male patient with a biopsy-proven cutaneous malignant melanoma located in the interscapular area was referred to lymphoscintigraphy for preoperative sentinel lymph node mapping. Anterior and posterior planar images showed 3 hot spots suggesting left axillary sentinel nodes. Herein, we reported the contribution of preoperative SPECT/CT-guided sentinel lymph node excision on accurate staging, management, prognostic evaluation, and determination of the proper surgical positioning preoperatively.
Keywords: malignant melanoma; lymphoscintigraphy; SPECT; CT; LYMPHOSCINTIGRAPHY; LOCALIZATION; EXCISION